if a^x= b^y = (ab)^(xy) prove that x+y =1

ln(a^x) = ln(b^y) = ln((ab)^(xy))
xln(a) = xyln(ab)
ln(a) = yln(ab) = y(ln(a) + ln(b))
y = ln(a)/(ln(a)+ln(b))
with same analysis for ln(b^y):
ln(b) = x(ln(a) + ln(b))x = ln(b)/(ln(a)+ln(b))
x + y = (ln(a) + ln(b))/(ln(a) + ln(b)) = 1

Answered by Scott C. Maths tutor

5020 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

How do I find the maxima and minima of a function?


Solve x^2=4(x-3)^2


Question 3 on the OCR MEI C3 June 2015 paper. Find the exact value of Integral x^3 ln x dx between 1 and 2.


Differentiate y = 15x^3 + 24x^2 + 6 with respect to x.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences